Integrated Algae Pond Systems for the Treatment of Municipal Wastewater - Mambo, Mutsa Prudence (Rhodes University, Faculty of Science, Institute for Environmental Biotechnology, 2016)
Integrated algae pond systems are a derivation of the Oswald designed advanced integrated wastewater ponding system, and combine the use of anaerobic and aerobic bioprocesses to effect wastewater treatment. Integrated algae pond system technology was introduced to South Africa in 1996 and a pilot plant was designed and commissioned at the Belmont Valley wastewater treatment works in Grahamstown. Previous studies showed that this system delivered a final effluent superior to most pond systems deployed in South Africa but that it was unable to meet the general standard for nutrient removal and effluent discharge. This study was initiated to re-appraise integrated algae pond systems and to assess the potential of the technology as an effective municipal sewage treatment system. And more...
Keywords: Uncatalogued